Implementation of Chemical Castration Sanctions: Legal Obstacles and a Human Rights Based Reconstruction - Rumesten, Iza; Muntaqo, Firman; Yuningsih, Henny; Rakhma Banjarani, Desia (Faculty of Law, Universitas Jambi, 2026)
There are various pros and cons of the chemical castration sanctions implementation, which raises various ideas so that the implementation of this sanction is more equitable and reduces the pros and cons. The purposed that will be discussed in this research are related to analyze the implementation of chemical castration sanctions in court decisions and what the obstacles in that implementation. Then another purpose is to formulated the idea of implementing chemical castration sanctions is based on the concept of human rights. The findings of this study propose the idea of enforcing chemical castration based on human rights, an idea previously unproven in research related to chemical castration. This research is normative legal research that uses a case approach and a statutory approach. The implementation of chemical castration sanctions against court decisions is based on three decisions that impose chemical castration sanctions on defendants who commit sexual violence against children. So, it can be seen that the judge's considerations in imposing chemical castration sanctions are due to several considerations. Inhibiting factors in the implementation of chemical castration sanctions are the rejection from various parties in Indonesia such as human rights activists and doctors. With these obstacles, it is necessary to reformulate the implementation of chemical castration sanctions in Indonesia which will be offered in this research, namely based on human rights. The application of chemical castration using a human rights approach is by implementing chemical castration oriented towards protection for perpetrators and oriented towards rehabilitation which is strengthened by a special law on chemical castration.